Titanium Alloys 2017 - Mark T. Whittaker (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Titanium is a good example of a material that is globally recognized for its outstanding properties, making it desirable for a range of industries. Titanium and its alloys are utilized in a wide range of industries, including aerospace, automotive and high performance leisure equipment. This Special Issue of Metals focusing on titanium contains a range of articles based on research into this fascinating material and its wide range of alloys. For applications that can withstand the high basic cost of titanium it is shown that the unique properties of the material have the potential to provide further performance improvements to existing industries, whilst offering new opportunities to emerging markets.